Marginal zone lymphoma causing accelerated progression of chronic kidney disease. Issue 11 (10th November 2019) - Samarasinghe, Amali; Wong, Daniel; Cull, Gavin; Chakera, Aron
Abstract : A 75-year-old man with stage IV chronic kidney disease due to type 2 diabetes mellitus, presented with increasing proteinuria and rapidly declining renal function despite excellent glycaemic control. Investigations organised to assess his suitability for renal transplantation included an abdominal CT scan, which revealed extensive intra-abdominal lymphadenopathy. A 17 fluorodeoxyglucose (FDG)-positron emission tomography scan to further characterise the lymphadenopathy demonstrated activity in the lymph nodes, as well as both kidneys. Following a lymph node biopsy and flow cytometry he was diagnosed with a marginal zone lymphoma. A subsequent kidney biopsy confirmed lymphomatous infiltration of the kidney. Marginal zone lymphoma is an uncommon type of non-Hodgkin's lymphoma, and renal involvement is rare. This case highlights the importance of considering alternative diagnoses when there is deviation from the expected clinical trajectory and the importance of liaising with colleagues in other disciplines to enable an accurate diagnosis to be made.